(NpOWESTI I RASSKAZY(B: [1903-1910] /s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(Nw TOM WO[LI POWESTI I RASSKAZY l(B. (NtOLSTOGO POSLEDNEGO PERIODA TWOR^ESTWA (B(1903-1919 (NGG(B.) - "(NpOSLE BALA(B", "(NhADVI(B-(NmURAT(B", "(NfALX[IWYJ KUPON(B" (NI DRUGIE(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs